History and modernity: about science over 50 years - A. I. Kozlov (Научный вестник МГТУ ГА)
The article presents the meaningful review of the half-century history of the scientific activity development at the Moscow State Technical University of Civil Aviation, from the date of the University establishment in 1971 up to the present. It is noted that originally the university was faced with the challenge of designing an organizational structure comprising research units, which was successfully solved, and consequently, two years later the first research findings emerged. The competent strategy of the University Authority and the Academic Senate focused on the main fields of scientific research for decades. Obtaining employment by the acclaimed Russian scientists at the University as well as involvement of gifted and promising post-graduate researchers with science facilitated the formation of the University scientific schools. The article features the most significant stages of the scientific school formation of I.S. Golubev, I.M. Sindeev, A.A. Kuznetsov, V.I. Vasiliev, V.G. Vorobyov, S.V. Kuznetsov, N.N. Smirnov, Yu.M. Chinyuchin, V.G. Tsipenko, I.V. Nikitin, V.S. Strelyaev, V.S. Shapkin, S.K. Kamzolov, A.I. Kozlov, A.I. Logvin, V.D. Rubtsov, V.V. Solomentsev, E.E. Nechaev, O.V. Repinoy, O.D. Garanina, B.P. Eliseev, V.V. Vorobyov, etc. It is noted that the international scientific cooperation; the Thesis Board activity; publications, authors’ certificates, patents, University researchers’ awards in respective fields of science, demonstrating the results of fundamental and applied research, contributed to the formation of the University scientific authority. The article deals with the key issues of the University science development during different years as well as the current day challenges. It is shown that these days the University has the considerable scientific potential, which is capable of both identifying industry-specific scientific problems and solving them.